ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA - Rodliyah, Syamsiati; Syaichu, Muhamad (Faculty of Economics and Business Diponegoro University, 2021)
Banks, especially Islamic banks, have a very important role in the wheels of economic turnover in Indonesia, the majority of which are Muslim. Bank as an intermediary institution channeling funds from excess parties to those in need. The development of Islamic banks in Indonesia is certainly inseparable from several factors that affect the improvement in performance. The purpose of this study is to analyze the effect of income diversification (ID), asset diversification (AD), bank fficiency (EFF), equity to assets (ETA) and non-performing financing (NPF) on return on assets (ROA) of Islamic banks. The population used as a sample in this study is Islamic commercial banks whose financial statements have been published to Bank Indonesia for the period 2014 to 2018. Sampling uses purposive sampling or intentional sampling for specific purposes. The data of this study uses secondary data derived from the websites of each bank and Bank Indonesia. The data analysis method used is multiple linear regression analysis. The results of this study indicate that asset diversification (AD), equity to assets (ETA) have a significant positive effect and bank fficiency (EFF) have a significant negative effect on return on assets (ROA). While variable income diversification (ID) and non-performing financing (NPF) have no effect at all on the variable return on assets (ROA).